Association of Candidate Genes With Submergence Response in Perennial Ryegrass - Wang, Xicheng; Jiang, Yiwei; Zhao, Xiongwei; Song, Xin; Xiao, Xiangye; Pei, Zhongyou; Liu, Huifen (Frontiers in Plant Science, 2017)
Perennial ryegrass is a popular cool-season grass species due to its high quality for forage and turf. The objective of this study was to identify associations of candidate genes with growth and physiological traits to submergence stress and recovery after de-submergence in a global collection of 94 perennial ryegrass accessions. Accessions varied largely in leaf color, plant height (HT), leaf fresh weight (LFW), leaf dry weight (LDW), and chlorophyll fluorescence (Fv/Fm) at 7 d of submergence and in HT, LFW and LDW at 7 d of recovery in two experiments. Among 26 candidate genes tested by various models, single nucleotide polymorphisms (SNPs) in 10 genes showed significant associations with traits including 16 associations for control, 10 for submergence, and 8 for recovery. Under submergence, Lp1-SST encoding sucrose:sucrose 1-fructosyltransferase and LpGA20ox encoding gibberellin 20-oxidase were associated with LFW and LDW, and LpACO1 encoding 1-aminocyclopropane-1-carboxylic acid oxidase was associated with LFW. Associations between Lp1-SST and HT, Lp6G-FFT encoding fructan:fructan 6G-fructosyltransferase and Fv/Fm, LpCAT encoding catalase and HT were also detected under submergence stress. Upon de-submergence, Lp1-SST, Lp6G-FFT, and LpPIP1 encoding plasma membrane intrinsic protein type 1 were associated with LFW or LDW, while LpCBF1b encoding C-repeat binding factor were associated with HT. Nine significant SNPs in Lp1-SST, Lp6G-FFT, LpCAT, and LpACO1 resulted in amino acid changes with 5 substitutions found in Lp1-SST under submergence or recovery. The results indicated that allelic diversity in genes involved in carbohydrate and antioxidant metabolism, ethylene and gibberellin biosynthesis, and transcript factor could contribute to growth variations in perennial ryegrass under submergence stress and recovery after de-submergence.